DANCE AND PHYSICAL DISABILITIES: A CASE STUDY (Fiep Bulletin - online, 2013)
The dance is a form of communication and expression, a manifestation of the inherent nature of man, the events in this life (NANNI, 2003). This study sought to investigate the effect of dance from the viewpoint of the disabled physically as well as its effects, reflecting on the prospect of nonverbal language that expresses the body. Brought from a qualitative approach and using only a participant from the male, with 27 years of age. As a tool to collect, intervention was done through dance and after that, semi-structured interview. The results showed the necessity that the bearer of physical disability has to communicate with the world through the body, because the motion allows the discovery of new possibilities. It is understood that the important role of exerts dancing reconstruction of their self-image, until then rejected, re-signifying their relationship with the body. Thus, studies of dance for the disabled physically become necessary. Therefore, it is suggested investing in shares with other studies in dance for people with disabilities, which extend the age groups and different demands.
Keywords: Dance; handicapped; Body Expression